2022
DOI: 10.1126/science.abf3326
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel p16 INK4a+ cells in the basement membrane form a reparative niche in the lung

Abstract: We engineered an ultrasensitive reporter of p16 INK4a , a biomarker of cellular senescence. Our reporter detected p16 INK4a -expressing fibroblasts with certain senescent characteristics that appeared shortly after birth in the basement membrane adjacent to epithelial stem cells in the lung. Furthermore, these p16 INK4a+ fibroblasts had enhanced capacity to sense tissue inflammation and respond through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…2C). Similar to recent findings using highly sensitive p16 Ink4a -reporter mice (INKBRITE) 37 , we found an inverse relationship between Ki67 and p16 expression (Extended Data Fig. 3B), which also revealed that clusters both high in p16 and low in Ki67 were defined by expression of BCL-2, a major regulator of apoptosis resistance 41 (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…2C). Similar to recent findings using highly sensitive p16 Ink4a -reporter mice (INKBRITE) 37 , we found an inverse relationship between Ki67 and p16 expression (Extended Data Fig. 3B), which also revealed that clusters both high in p16 and low in Ki67 were defined by expression of BCL-2, a major regulator of apoptosis resistance 41 (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Although long-established as a marker of senescence, we found that p16 expression labels a diverse set of cells with both senescent and non-senescent properties. This finding is entirely consistent with recent findings using highly sensitive p16 Ink4a reporter mice (INKBRITE) 37 , although we provide important complementary data at the protein level to the transcriptional data in the previous study. Specifically, similar to our finding of p16 protein expression in both Ki67 negative and positive bone and marrow mesenchymal cells, in the INKBRITE p16 Ink4a reporter mice, p16 Ink4a was also expressed in both proliferating and non-proliferating lung fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the use of senolytic drugs to treat cancers is complicated by the fact that our understanding of how senescent fibroblasts can impact normal (non-cancerous) cells remains quite limited. For example, recent evidence suggests that senescent fibroblasts in the lung can sense injury-induced tissue inflammation, alter the stem cell niche, and facilitate the regeneration of epithelial barrier integrity (30). Therefore, additional studies that better clarify the relationship between senescent fibroblasts and non-cancerous epithelial cells are critically important to better understand the efficacy of this therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%